Study on the Synthesis of Chabazite Zeolites via Interzeolite Conversion of Faujasites - Long Van Dang; Thu Thi Minh Nguyen; Dang Van Do; Son Thanh Le; Trong Dinh Pham; Anh Thi Mai Le (Journal of Analytical Methods in Chemistry)
The interzeolite conversion of faujasite (FAU-type) zeolites to chabazite (CHA-type) zeolite in the presence of N,N,N-trimethyladamantammonium and N,N,N-dimethylethylcyclohexylammonium cations was investigated over a large compositional range by carefully controlling the reaction mixture compositions. Highly crystalline CHA zeolites were also obtained by the transformation of several zeolite types including EMT, LTL, LEV, RTH, and MFI frameworks. The formation of CHA zeolite from FAU zeolite precursors was substantially faster than that from zeolite L with a similar composition. High-silica CHA zeolites were also produced successfully using a mixture of TMAda with a number of less expensive organic structure-directing agents. The CHA zeolite materials have been synthesized with high crystallinity and with a Si/Al ratio ranging from 5 to 140. Our data support the importance of structural similarity between the zeolite precursors, nucleation/crystallization processes, and the zeolite product in the interzeolite conversion compared to conventional amorphous aluminosilicate gels. Our synthetic methods could be used to prepare other 8-membered ring zeolites such as AEI and AFX frameworks, potential candidates for selective catalytic reduction of NOx, light olefin production, and CO2 abatement.